Enhancing Transportation Literacy Through English Language Acquisition - Marudut Bernadtua Simanjuntak (International Journal of Multilingual Education and Applied Linguistics, 2024)
This research investigates the impact of English language acquisition on transportation literacy among transportation management students. Through qualitative analysis of interviews and document analysis, the study explores how proficiency in English influences students' comprehension of key transportation concepts. The findings reveal that English language proficiency significantly enhances students' understanding of complex transportation topics, such as logistics, safety regulations, and multimodal transportation systems. Integrating effective language learning strategies, such as real-world scenarios and interactive activities, into transportation management courses can bridge the gap between language proficiency and transportation literacy. Additionally, innovative assessment methods, such as performance-based assessments, offer a more comprehensive approach to evaluating students' language proficiency and its application in transportation contexts. The study recommends ongoing professional development for educators, collaboration with industry partners, and the promotion of multilingualism to enhance transportation literacy among students. By adopting these recommendations, educational institutions can ensure that transportation management students are equipped with the necessary language skills to succeed in an increasingly globalised and diverse transportation industry.